Comparison of Surgical Outcomes Associated With Compression Secondary to Hemorrhage and Intervertebral Disk Extrusions in Dogs - Lawler, Patricia E.; Wood, Jonathan H.; Alleva, Nicole E.; Rishniw, Mark; Porter, Ian; Johnson, Phillipa J. (Frontiers in Veterinary Science, 2022)
Acute intervertebral disk extrusion (IVDE) is one of the most commonly reported neurologic disorders seen in veterinary practice. There is a recognized subset of IVDE cases that have a hemorrhagic inflammatory reaction within the epidural space that causes compression in addition to compression from herniated disk material. Previous reports have been conflicting in the outcomes of these cases. The goals of this retrospective case-control cross-sectional study are to (1) compare the success rate of routine surgical decompression in dogs with DEEH compression compared to Modified Frankel Score (MFS) matched dogs with non-hemorrhagic disk extrusions; (2) evaluate the extent of spinal cord compression on MRI compared to final patient outcomes in DEEH compression and (3) determine the surgical compression to decompression ratio and its relation to patient outcomes in cases of DEEH compression. A total of 143 dogs were included in this study and divided into two groups: DEEH compression dogs (n = 78) and non-hemorrhagic IVDE dogs (n = 65). Outcomes were assigned for each patient [0 = deceased, 1 = alive and non-ambulatory (MFS 0–3), 2 = alive and ambulatory (MFS 4 or 5)] in both groups. Outcomes of DEEH and non-hemorrhagic IVDE did not differ when taken to surgery with comparable success rates when stratified by MFS. Similarly, outcomes did not differ between DEEH and non-hemorrhagic IVDE dogs when assessed by compression to decompression ratio. Dogs with DEEH compression had more compressed sites than dogs with non-hemorrhagic IVDE (P = 0.001) and had more sites decompressed surgically than dogs with non-hemorrhagic IVDE (P < 0.001). Consequently, the compression to decompression ratio did not differ between the two groups (P = 0.52). Our results support the finding that when a similar level of surgical decompression is achieved, dogs with DEEH compression have similar outcomes to dogs with non-hemorrhagic IVDE for similar degrees of neurological dysfunction.